Issues of ex situ plant diversity conservation in Albania - Dinga L.; Hoda P.; Sulovari H.; Abeshi P. (Italo-Albanian cooperation for the enhancement of plant biodiversity, 2001)
The objective of this study is to provide information about the current situation of the plant diversity preservation in Albania, focusing on the ex situ conservation of the wild and cultivated plants. Until 1990 about 1,600 wild species, 587 cultivated species with nearly 20,500 accessions were preserved. This study deals with the main reasons that make ex situ plant conservation in Albania a necessity for the future. It covers an analysis of the relevant current issues and also the future action plan which targets both, on the establishment of a national body of representatives from the concerned institutions of germplasm preservation and on the formulation of the Albania ex situ plant preservation strategy as an alternative and supplement to the in situ conservation.
2. Seminar: Italo-Albanian cooperation for the enhancement of plant biodiversity, 2000/10/26-28, Tirana (Albania)